The Role of Financial Technology (Fintech) in Improving Financial Inclusion - Ernawati (Universitas Muhammadiyah Palu, 2025)
Financial Technology (Fintech) plays a crucial role in enhancing financial inclusion in Indonesia by providing easier and more affordable access to financial services, particularly for communities previously marginalized by traditional banking systems. Through digital innovations such as digital payments, peer-to-peer (P2P) lending, and technology-based investments, fintech creates new opportunities for the public to access financial products. However, challenges related to data security and financial literacy remain significant barriers that need to be addressed. This article discusses how fintech contributes to improving financial inclusion in Indonesia, identifies its benefits, and reviews the challenges encountered in its implementation. With proper regulation and increased financial literacy, fintech can accelerate the achievement of more equitable financial inclusion.